2000
DOI: 10.1111/j.1348-0421.2000.tb02561.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Ratio between Borna Disease Viral‐p40 and ‐p24 Proteins in Infected Cells Determined by Quantitative Antigen Capture ELISA

Abstract: We developed the antigen capture enzyme-linked immunosorbent assay (ELISA) systems for quantification of Borna disease virus (BDV) major antigens, p40 and p24. Using these ELISAs, we quantified the two proteins in various BDV-infected materials, including the cell lysates and culture supernatants as well as the homogenates of experimental animal brains. The ELISAs were also applied to measure the infectious titer of BDV in persistently infected cell lines. Quantitative analysis with these ELISAs allowed us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…We have reported changes in the N/P ratio during the different stages of BDV infection (32,33). Intriguingly, in BDV persistently infected cells, P was found to be present in about an eightfold molar excess over N (32).…”
Section: Discussionmentioning
confidence: 97%
“…We have reported changes in the N/P ratio during the different stages of BDV infection (32,33). Intriguingly, in BDV persistently infected cells, P was found to be present in about an eightfold molar excess over N (32).…”
Section: Discussionmentioning
confidence: 97%
“…7). In fact, we have recently demonstrated that the molecular ratio between the N and P proteins is significantly different between persistently and acutely BDV-infected cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…As probes, 6 g of glutathione S-transferase (GST)-p24, GST, or purified p24 protein produced from Escherichia coli per ml was allowed to bind to blotted proteins in PBS-T containing 5% (wt/vol) skimmed milk overnight at 4°C. The expression and purification of the recombinant GST-p24 and removal of GST from GST-p24 were described elsewhere (51). The blots were washed three times with PBS-T for 30 min and were then reacted with anti-GST mouse monoclonal antibody (MAb) or anti-p24 rabbit polyclonal antibody (PAb) in PBS-T containing 5% skimmed milk for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%